The “hairy beast”—Zorotypus hirsutus sp. n., an unusual new species of Zoraptera (Insecta) from Burmese amber - Mashimo, Yuta; Müller, Patrick; Pohl, Hans; Beutel, Rolf G. (Zootaxa, 2018)
A new species of the order Zoraptera, Zorotypus hirsutus Mashimo sp. n., is described from mid-Cretaceous Burmese amber. The specimen is tentatively assigned to the subgenus Octozoros Engel based on number of antennomeres reduced from nine to eight. It is characterized by an unusually strong setation, appearing much more hirsute than other extant or extinct species of the order. Other unusual autapomorphic features are an elongated head capsule with a concave genal region and very slender, elongate antennomeres. The discovery of this aberrant species suggests that the morphological diversity of Zoraptera was much higher than previously expected. For a reliable placement of Zorotypus hirsutus the discovery of males and a robust species level phylogeny would be required.